Preparation method and application of zirconium dioxide loaded iridium oxide nanocluster oxygen evolution electrocatalyst
By using the oxidation nano -clustered oxygen catalyst with oxidation nano -catalytic catalyst with a stable tetramidal crystalline oxidation load load in the hydrolysis of the proton exchange membrane, solve the high cost of the cymbal material in the existing technology The problem of sexual balance realizes efficient and stable oxygen analysis and electrolytic water production that has been running for a long time.
Patent Information
- Application Number
- CN202411314268.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The iridium-based materials used in water electrolysis of existing proton exchange membranes hinder the further application of this technology due to their low natural abundance and high cost. Most oxygen-elimination electrocatalysts follow the adsorption oxygen oxidation mechanism, resulting in a trade-off in activity and stability. It is impossible to operate continuously in a proton exchange membrane electrolytic cell for a long time.
Adopt the preparation method of oxidation nanomantic catalysts based on oxide nanoplasty catalysts with oxidation-oxidation nanotransomed oxygen catalysts based on oxygen-based crystalline phase phase, use the crystal oxygen oxidation mechanism to form a*OO2-intermediate, stabilize stability Catalyst structure, enhance activity and stability.
Achieve efficient and stable oxygen analysis in proton exchange membrane electrolytes, reduce the load of the pupa, and improve the utilization efficiency of catalysts. It can run continuously for 1600 hours at 1.0A · CM-2 current density. The attenuation rate is only 6.25 μV. · H-1.
Smart Images

Figure CN119352065A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysts, and relates to a method for preparing an iridium oxide nanocluster oxygen evolution electrocatalyst based on tetragonal zirconium dioxide supported on oxygen overflow stabilization, and also relates to its application in preparing an electrocatalyst for oxygen evolution reaction in an acidic electrolyte, and in proton exchange membrane water electrolysis oxygen absorption electrode, and also has potential application value in other fields such as energy development and environmental protection. Background Art
[0002] Proton exchange membrane water electrolysis plays an important role in converting renewable energy into green hydrogen due to its high current density and fast response. However, commercial anode electrocatalysts based on iridium-based materials have largely hindered the further application of this technology due to the low natural abundance and high cost of iridium. Therefore, reducing the iridium loading is crucial for the large-scale implementation of proton exchange membrane water electrolysis.
[0003] In previous studies, tuning the oxygen evolution reaction pathway can effectively mediate the trade-off between activity and stability, and the lattice oxygen oxidation mechanism can directly form *OO 2- The oxygen-containing intermediates are formed without forming the intermediates *OOH of the adsorbed oxygen oxidation mechanism, thus breaking the linear relationship between oxygen-containing intermediates and oxidation overpotential. However, the participation of lattice oxygen will also produce soluble high-valent metal oxides, resulting in poor collapse stability of the catalyst structure. Therefore, most of the oxygen evolution electrocatalysts currently developed are adjusted to follow the adsorbed oxygen oxidation mechanism to meet the requirements of PEM electrolyzers, which inevitably sacrifices activity. The oxygen overflow mechanism can make the oxygen intermediates adsorbed on the inert support overflow to the iridium site, thereby stabilizing the catalyst structure and synergistically enhancing activity and stability. Summary of the invention
[0004] The present invention is aimed at the above problems, and aims to provide a preparation method and application of iridium oxide nanocluster oxygen evolution electrocatalyst supported by tetragonal zirconium dioxide with oxygen overflow stability, provide a new design idea of precious metal-based supported materials, and realize the economical, efficient and sustainable development of proton exchange membrane water electrolysis. The catalyst material preparation method is simple and low in cost, can be synthesized in large quantities, and has the potential for efficient and stable oxygen evolution, and has the potential for large-scale industrial application.
[0005] In order to achieve the above object, the technical solutions specifically adopted by the present invention are as follows:
[0006] In a first aspect, the present invention provides a method for preparing a zirconium dioxide-supported iridium oxide nanocluster oxygen evolution electrocatalyst, comprising the following steps:
[0007] A. Preparation of Zirconium Dioxide Support
[0008] A mixed solution of zirconium salt, amide solvent and organic acid is prepared, kept at 120°C for 24 hours, and then cooled to room temperature. The white product is centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol for multiple times, and dried in a vacuum oven at 60°C for 12 hours to obtain a white powder;
[0009] B. Iridium Oxide Nanocluster Loading
[0010] The iridium salt is dispersed in a mixed solvent of tetrahydrofuran and water, and then the white powder is added, stirred for 24 hours, and then a mixed solution of sodium nitrate and potassium nitrate is added, stirred for 30-40 minutes, and the solvent is removed by rotary evaporation at 60°C, and the mixture is placed in a vacuum oven at 60°C for drying for 12 hours; the dried light green powder is placed in a muffle furnace at 450°C for insulation for 30-40 minutes, and then directly taken out and cooled in the air, the product is washed with deionized water and anhydrous ethanol for multiple times, and finally dried in a vacuum oven at 60°C for 12 hours to obtain the electrocatalyst.
[0011] Preferably, the preferred process conditions of the above steps are as follows:
[0012] (1) Step A
[0013] The zirconium salt is selected from any one or more combinations of zirconium nitrate, zirconium tetrachloride, and zirconium oxynitrate; the amide is selected from any one or more combinations of N,N'-dimethylformamide, N,N'-dimethylacetamide, and N,N'-dimethylacrylamide; and the organic acid is selected from any one or more combinations of benzoic acid, formic acid, and terephthalic acid.
[0014] Furthermore, in a specific embodiment of the present invention, the organic acid is selected from a mixture of terephthalic acid and benzoic acid, and the molar ratio of terephthalic acid to benzoic acid is 0.09 to 0.1:1; the mass volume ratio between the zirconium salt and the amide is 13 to 13.5 g / L, and the molar ratio between the zirconium salt and terephthalic acid is 1 to 1.1:1.
[0015] (2) Step B
[0016] The volume ratio of tetrahydrofuran to water is 1:1, and the concentration of iridium salt in the mixed solvent is 1 g / L; the mass ratio of white powder to iridium salt is 0.4-1.1:1; the mass ratio of sodium nitrate to potassium nitrate is 6:4, and the mass ratio of iridium salt to the mixture of sodium nitrate and potassium nitrate is 3:100.
[0017] In a second aspect, the present invention provides a zirconium dioxide supported iridium oxide nanocluster oxygen evolution electrocatalyst (IrO x / t-ZrO 2 ), which is prepared by the above method.
[0018] Transmission electron microscopy analysis results show that the electrocatalyst morphology is nanoparticles supported by porous nanostructures. The size of the nanoparticles is about 1.33 nanometers, and the iridium loading is 0.1 mg / cm 2 ; Since the atomic number Z of iridium is greater than that of zirconium, the distribution of iridium can be directly determined by Z comparison. It can be seen that iridium oxide is nanoclusters loaded on tetragonal zirconium dioxide.
[0019] The results of X-ray diffraction analysis show that the characteristic diffraction peaks at angles of 30.2°, 50.2°, and 60.2° correspond to the (101), (112), and (211) crystal planes of the tetragonal zirconium dioxide crystal. After loading iridium oxide, the peak intensity near about 35° is enhanced, which is the (101) crystal plane of the iridium dioxide crystal.
[0020] After applying different voltages to the material, it was found that the Ir-O bond also shortened after the voltage was applied, indicating that the coordination structure of iridium rearranged and reacted through the lattice oxygen mechanism. During the oxygen evolution reaction, the coordination number of Zr-O also decreased, indicating the occurrence of oxygen overflow, but the oxygen vacancies could be quickly filled, thus avoiding the structural collapse that could be caused by oxygen vacancies.
[0021] The material of the invention can be applied to electrocatalytic oxygen evolution reaction under acidic electrolyte conditions and in proton exchange membrane electrolyzers under pure water conditions.
[0022] Electrochemical performance test: using IrO x / t-ZrO 2 The glassy carbon electrode of the catalyst was used as the working electrode, the silver-silver chloride electrode was used as the reference electrode, the platinum mesh electrode was used as the counter electrode, and the electrolyte solution was 0.5 M HClO 4 Electrochemical tests were carried out at room temperature and pressure. The results showed that the mass activity of the catalyst at 1.55V and 1.60V was 609.1A g Ir -1 and 1457.4Ag Ir -1 , and far exceeds the commercial iridium black material of Comparative Example 3 (46.7Ag Ir -1 and 110.7Ag Ir -1 ), indicating that metallic iridium in IrO x / t-ZrO 2 There is a higher utilization efficiency.
[0023] It was prepared into anode electrode material for proton exchange membrane electrolyzer, and full battery test was carried out in proton exchange membrane acidic water electrolyzer to simulate industrial water electrolysis environment. The results showed that the Ir loading contained was only 0.1 mg cm -2The assembled proton exchange membrane electrolyzer can reach 3.1A·cm at a voltage of 1.9V -2 The current density is 1A·cm -2 It can run stably for 1600 hours at a current density of 1.500V / h, and the decay rate is only 6.25μV·h -1 .
[0024] Therefore, the third aspect of the present invention provides the use of the above-mentioned zirconium dioxide-supported iridium oxide nanocluster oxygen evolution electrocatalyst in the preparation of an acidic electrolytic oxygen evolution electrode.
[0025] In a fourth aspect, the present invention provides an acidic electrolytic oxygen evolution anode electrode, comprising an anode carrier and a catalyst material loaded thereon, wherein the catalyst material is an iridium oxide nanocluster oxygen evolution electrocatalyst loaded with zirconium dioxide prepared by any of the methods described above.
[0026] In a fifth aspect, the present invention provides a method for electrolyzing water, using the above-mentioned electrolytic oxygen-decomposing anode electrode as an anode.
[0027] Preferably, the electrolyte is 0.5M HClO 4 solution or deionized water.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) So far, most of the acidic oxygen evolution electrocatalysts developed following the lattice oxygen pathway cannot sustain the harsh environment under practical proton exchange membrane water electrolysis conditions. This invention provides new insights into the lattice oxygen pathway for oxygen spillover stability for the first time and successfully constructs a new low-iridium anode electrocatalyst that can operate continuously in a proton exchange membrane electrolyzer.
[0030] (2) IrO prepared by the present invention x / t-ZrO 2 Electrocatalyst as anode material (0.1 mg Ir cm -2 ) assembled PEM electrolyzer reached 3.1A·cm at a cell voltage of 1.90V -2 The current density is 1.0A·cm -2 The results show that IrO x / t-ZrO 2 Reach 3.1A·cm -2 The voltage and noble metal loading required for the current density are superior to those of state-of-the-art PEM anode electrocatalysts.
[0031] (3) The catalyst material preparation method prepared by the present invention is simple and low-cost, can be synthesized in large quantities, and has the potential for efficient and stable oxygen evolution, and has the potential for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The IrO prepared in Example 1 x / t-ZrO 2 and t-ZrO prepared in Example 2 2 X-ray diffraction pattern of the material.
[0033] Figure 2 The IrO prepared in Example 1 x / t-ZrO 2 Transmission electron microscopy image of the material.
[0034] Figure 3 The IrO prepared in Example 1 x / t-ZrO 2 Spherical aberration corrected high-angle annular dark-field scanning transmission microscopy image of the material.
[0035] Figure 4 IrO prepared in Example 1, Comparative Example 1 and Comparative Example 2 x / t-ZrO 2 The iridium L3 edge in-situ X-ray absorption fine structure near-edge spectrum and its magnified image and R space spectrum of the material, where comparative example 1 is IrO after applying a voltage of 1.5V x / t-ZrO 2 Materials, Comparative Example 2 is IrO after applying 1.7V voltage x / t-ZrO 2 Material.
[0036] Figure 5 IrO prepared in Example 1, Comparative Example 1 and Comparative Example 2 x / t-ZrO 2 The zirconium K-edge in-situ X-ray absorption fine structure near-edge spectrum and its magnified image and R space spectrum of the material, where Comparative Example 1 is IrO after applying a voltage of 1.5V x / t-ZrO 2 Materials, Comparative Example 2 is IrO after applying 1.7V voltage x / t-ZrO 2 Material.
[0037] Figure 6 The linear sweep voltammetric comparison curves of the materials of Examples 1, 2, 3 and Comparative Example 3 in the three-electrode test system, wherein Example 1 is IrO with an iridium content of 20 wt%. x / t-ZrO 2Material, Example 2 is IrO with an iridium content of 30wt% x / t-ZrO 2 Material, Example 3 is IrO with an iridium content of 50wt% x / t-ZrO 2 Materials, Comparative Example 3 is commercial iridium black material.
[0038] Figure 7 The IrO prepared in Example 1 x / t-ZrO 2 The mass activity of the material is compared with that of the material of Comparative Example 3 at voltages of 1.55 V and 1.6 V relative to the standard hydrogen electrode, wherein Comparative Example 3 is an iridium black material.
[0039] Figure 8 The IrO prepared in Example 1 x / t-ZrO 2 Current density-voltage curve of the material as anode catalyst in proton exchange membrane water electrolysis device.
[0040] Fig. 9 The IrO prepared in Example 1 x / t-ZrO 2 The material was used as anode catalyst in proton exchange membrane water splitting device at 1A·cm -2 Constant current curve under current density. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The "range" disclosed herein is in the form of a lower limit and an upper limit. It can be one or more lower limits, and one or more upper limits, respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e., any lower limit can be combined with any upper limit to form a range. For example, a range of 100 to 140 and 500 to 900 is listed for a particular parameter, and it is understood that a range of 100 to 140 and 500 to 900 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum ranges 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 2, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5.
[0043] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0044] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0045] 1. Preparation of Catalyst Materials
[0046] Example 1 Preparation of Iridium Oxide Nanoclusters Supported on Tetragonal ZrO2 for Oxygen Evolution Electrocatalyst Based on Oxygen Overflow Stabilization
[0047] (1) dissolving cobalt chloride hexahydrate in deionized water to prepare a cobalt chloride hexahydrate aqueous solution with a concentration of 2 mol / L as solution A;
[0048] (2) At the same time, a certain amount of potassium ferricyanide reagent is weighed, and the weight weighed is in a molar ratio of 2:1 to the amount of cobalt chloride hexahydrate used in solution A, and is used as reagent B;
[0049] (3) Slowly add reagent B to solution A under light-proof and stirring conditions. After sufficient reaction, place the electrode support substrate in the mixed suspension. The substrate size is 10 cm 2 / 30mL mixed suspension, let stand for aging reaction at 60℃ in the dark without any interference for 6 hours;
[0050] (4) The electrode support substrate after the reaction is repeatedly rinsed with deionized water and ethanol, and naturally dried and oxidized in an air environment, thereby obtaining a catalyst precursor (a traditional bimetallic Prussian blue analogue) grown on the electrode support substrate;
[0051] (5) The catalyst precursor was continuously treated with oxygen plasma in the chamber of a radio frequency plasma enhanced chemical vapor deposition (RF-PECVD) system for 30 minutes, while the chamber pressure was maintained at 50 Pa and the RF plasma discharge power was 200 W, to obtain zirconium dioxide-supported iridium oxide nanoclusters for oxygen evolution electrocatalysis.
[0052] Example 2
[0053] The operating steps of Example 1 were repeated, except that in step (4), iridium trichloride powder was not added.
[0054] Example 3
[0055] The operating steps of Example 1 were repeated, except that in step (4), the mass of the white powder was 24.2 mg.
[0056] Example 4
[0057] The operating steps of Example 1 were repeated, except that in step (4), the mass of the white powder was 48.3 mg.
[0058] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
[0059] Comparative Example 1
[0060] The operating steps of Example 1 were repeated, except that a voltage of 1.5 V was applied to the synthesized catalyst material.
[0061] Comparative Example 2
[0062] The operating steps of Example 1 were repeated, except that a voltage of 1.7 V was applied to the synthesized catalyst material.
[0063] Comparative Example 3
[0064] Commercial iridium black purchased from the market was used as the anode catalyst for water electrolysis, and the electrocatalytic oxygen evolution performance test conditions were the same as those in Example 1.
[0065] 2. Performance Characterization Test
[0066] Figure 1 The iridium oxide nanocluster oxygen evolution electrocatalyst IrO based on the tetragonal zirconium dioxide supported by oxygen overflow stabilization prepared in Example 1 x / t-ZrO 2 and the X-ray diffraction pattern of the tetragonal zirconium dioxide prepared in Example 4. Figure 1 It can be seen that the characteristic diffraction peaks at angles of 30.2°, 50.2°, and 60.2° correspond to the (101), (112), and (211) crystal planes of the tetragonal zirconium dioxide crystal. After loading iridium oxide, the peak intensity near about 35° is enhanced, which is the (101) crystal plane of the iridium dioxide crystal.
[0067] Figure 2 The iridium oxide nanocluster oxygen evolution electrocatalyst IrO based on the tetragonal zirconium dioxide supported by oxygen overflow stabilization prepared in Example 1 x / t-ZrO 2 Transmission electron microscopy image of Figure 2 It can be seen that the catalyst has a porous structure.
[0068] Figure 3The iridium oxide nanocluster oxygen evolution electrocatalyst IrO based on the tetragonal zirconium dioxide supported by oxygen overflow stabilization prepared in Example 1 x / t-ZrO 2 Spherical aberration corrected high-angle annular dark-field scanning transmission microscopy image. Figure 3 It can be seen that the observed d spacing of 0.298 nm corresponds to the (101) crystal plane of tetragonal zirconium dioxide. Since the atomic number Z of iridium is greater than that of zirconium, the distribution of iridium can be directly determined by Z comparison, and it can be seen that iridium oxide is supported as nanoclusters on tetragonal zirconium dioxide.
[0069] Figure 4 IrO prepared in Example 1, Comparative Example 1 and Comparative Example 2 x / t-ZrO 2 The iridium L3 edge in-situ X-ray absorption fine structure near-edge spectrum and its magnified image and R space spectrum of the material, where comparative example 1 is IrO after applying a voltage of 1.5V x / t-ZrO 2 Materials, Comparative Example 2 is IrO after applying 1.7V voltage x / t-ZrO 2 Material.
[0070] After voltage is applied, the white line peak is enhanced and shifted positively, showing a rapid increase in the valence state of iridium. This is attributed to the movement of more electrons from iridium to nearby adsorbed oxygen, which then promotes the oxidation reaction through the lattice oxygen mechanism. However, when the voltage is further increased, the white line peak hardly changes, indicating that the valence state of iridium is stable during the oxygen evolution reaction. This finding suggests that the catalyst structure can avoid collapse caused by the formation of oxygen vacancies due to the overflow of oxygen from the support to the infrared position. The Ir-O bond also becomes shorter after voltage is applied, indicating that the coordination structure of iridium rearranges and reacts through the lattice oxygen mechanism. During the oxygen evolution reaction, oxygen vacancies can be quickly filled, thereby avoiding the structural collapse that may be caused by oxygen vacancies.
[0071] Figure 5 IrO prepared in Example 1, Comparative Example 1 and Comparative Example 2 x / t-ZrO 2 The zirconium K-edge in-situ X-ray absorption fine structure near-edge spectrum and its magnified image and R space spectrum of the material, where Comparative Example 1 is IrO after applying a voltage of 1.5V x / t-ZrO 2 Materials, Comparative Example 2 is IrO after applying 1.7V voltage x / t-ZrO 2When the applied potential increases, the white line peak shifts negatively and the valence state of zirconium decreases, indicating that the oxygen intermediates on the zirconium surface overflow to iridium. During the oxygen evolution reaction, the coordination number of Zr-O also decreases, indicating the occurrence of oxygen overflow.
[0072] 3. Electrochemical performance test
[0073] Ir x / t-ZrO 2 All electrochemical hydrogen evolution performance tests of the catalyst were carried out in a three-electrode system, with a platinum mesh as the counter electrode, Ag / AgCl as the reference electrode, and a IrO-coated x / t-ZrO 2 The glassy carbon electrode of the catalyst was used as the working electrode. Example 1 Materials 2.5 mg of catalyst powder was taken out and added to 960 μl of isopropanol, and then 40 μl of 5 wt% The solution was kept at 30 degrees Celsius and ultrasonicated for 30 minutes in an ultrasonic cleaner to make the catalyst slurry evenly dispersed. Then 5 microliters of slurry was taken out with a micro-injector and dripped onto the glassy carbon electrode. It was placed in a ventilated place for 15 minutes and then dried naturally. The electrochemical workstation used was Chenhua CHI 760E, and the electrolyte solution was 0.5M HClO 4 , electrochemical tests were carried out at room temperature and pressure.
[0074] Figure 6 The linear sweep voltammetric comparison curves of the materials of Examples 1, 2, 3 and Comparative Example 3 in the three-electrode test system are shown in FIG. Figure 6 It can be seen that with the increase of iridium loading, the performance of Experimental Examples 2 and 3 is not much different from that of Experimental Example 1. Example 1 can reach 10 mA cm at an overpotential of 288 mV. -2 The current density is better than that of the commercial iridium black in Comparative Example 3.
[0075] Figure 7 The IrO prepared in Example 1 x / t-ZrO 2 The mass activity of the material is compared with that of the material of comparative example 3, wherein comparative example 3 is a commercial iridium black material. Figure 7 It can be seen that the mass activities of the catalyst in Example 1 at 1.55 V and 1.60 V are 609.1 A·g Ir -1 and 1457.4A·g Ir -1 , and far exceeds the commercial iridium black material of Comparative Example 3 (46.7 A·g Ir -1 and 110.7A·g Ir -1 ), indicating that metallic iridium in IrO x / t-ZrO2 There is a higher utilization efficiency.
[0076] 4. Industrial electrolysis water simulation
[0077] IrO was tested using a proton exchange membrane electrolyzer system x / t-ZrO 2 The electrocatalytic performance of the anode catalyst is IrO x / t-ZrO 2 Catalyst: The cathode catalyst used was commercial 40% Pt / C. 5 mg of the powder catalyst of Example 1 was weighed and mixed with 47 μl of 5 wt% The anode catalyst slurry was prepared by mixing the isopropanol and deionized water solution. Then 10 mg of commercial 40% Pt / C was weighed and mixed with 27 μl of 5wt% The cathode catalyst slurry was prepared in isopropanol and deionized water of the solution. The two were ultrasonicated in a low-temperature water bath for at least 30 minutes to obtain a homogeneous catalyst slurry. The anode and cathode catalyst slurries were then sprayed on polytetrafluoroethylene respectively, and after drying, the catalysts were transferred to both sides of the Nafion115 / 212 proton exchange membrane using a hot press. After tearing off the polytetrafluoroethylene, the cathode and anode electrode materials of the proton exchange membrane electrolyzer were obtained. The anode iridium metal loading was 0.1 mg cm -2 Finally, the carbon paper and titanium felt were assembled into a proton exchange membrane electrolyzer for testing. The electrolyte solution was deionized water, the test temperature was 80 °C, and the flow rate was 30 mL min -1 .
[0078] Figure 8 The IrO prepared in Example 1 x / t-ZrO 2 Current density-voltage curve of the material as anode catalyst in proton exchange membrane water electrolysis device. Figure 7 It can be seen that the assembled proton exchange membrane electrolyzer can reach 3.1A·cm at a voltage of 1.9V. -2 The current density of IrO x / t-ZrO 2 The material has high catalytic activity under high current density in proton exchange membrane electrolyzer.
[0079] Fig. 9 The IrO prepared in Example 1 x / t-ZrO 2 The material was used as anode catalyst in proton exchange membrane water splitting device at 1A·cm -2 Constant current curve under current density. Figure 8 It can be seen that the assembled proton exchange membrane electrolyzer is 1A·cm -2After continuous operation for 1600 hours at the current density, the decay rate was only 6.25μV / h, indicating that the catalyst has significant potential in the practical application of proton exchange membrane hydrogen production.
[0080] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing a zirconium dioxide supported iridium oxide nanocluster oxygen evolution electrocatalyst, characterized in that: The steps include: A. Preparation of Zirconium Dioxide Support A mixed solution of zirconium salt, amide solvent and organic acid is prepared, kept at 120°C for 24 hours, and then cooled to room temperature. The white product is centrifuged, washed with N,N-dimethylformamide and anhydrous ethanol for multiple times, and dried in a vacuum oven at 60°C for 12 hours to obtain a white powder; B. Iridium Oxide Nanocluster Loading The iridium salt is dispersed in a mixed solvent of tetrahydrofuran and water, and then the white powder is added, stirred for 24 hours, and then a mixed solution of sodium nitrate and potassium nitrate is added, stirred for 30-40 minutes, and the solvent is removed by rotary evaporation at 60°C, and the mixture is placed in a vacuum oven at 60°C for drying for 12 hours; the dried light green powder is placed in a muffle furnace at 450°C for insulation for 30-40 minutes, and then directly taken out and cooled in the air, the product is washed with deionized water and anhydrous ethanol for multiple times, and finally dried in a vacuum oven at 60°C for 12 hours to obtain the electrocatalyst.
2. The preparation method according to claim 1, characterized in that: in, In step A, the zirconium salt is selected from any one or more combinations of zirconium nitrate, zirconium tetrachloride, and zirconyl nitrate; The amide is selected from any one or more combinations of N,N'-dimethylformamide, N,N'-dimethylacetamide, and N,N'-dimethylacrylamide; The organic acid is selected from any one or more combinations of benzoic acid, formic acid and terephthalic acid.
3. The preparation method according to claim 2, characterized in that: in, The organic acid is selected from a mixture of terephthalic acid and benzoic acid, and the molar ratio of terephthalic acid to benzoic acid is 0.09 to 0.1:1; The mass volume ratio between the zirconium salt and the amide is 13-13.5 g / L, and the molar ratio between the zirconium salt and terephthalic acid is 1-1.1:
1.
4. The preparation method according to claim 1, characterized in that: in, In step B, the volume ratio between tetrahydrofuran and water is 1:1, and the concentration of iridium salt in the mixed solvent is 1 g / L; The mass ratio between the white powder and the iridium salt is 0.4 to 1.1:1; The mass ratio of sodium nitrate to potassium nitrate is 6:4, and the mass ratio of iridium salt and the mixture of sodium nitrate and potassium nitrate is 3:
100.
5. A zirconium dioxide supported iridium oxide nanocluster oxygen evolution electrocatalyst, characterized in that: The method is prepared by any one of claims 1 to 4.
6. The zirconium dioxide supported iridium oxide nanocluster oxygen evolution electrocatalyst according to claim 5, characterized in that: The electrocatalyst morphology is nanoparticles supported by a porous nanostructure. The nanoparticle size is about 1.33 nanometers and the iridium loading is 0.1 mg / cm 2 .
7. Use of the zirconium dioxide supported iridium oxide nanocluster oxygen evolution electrocatalyst according to claim 6 in the preparation of an acidic electrolytic oxygen evolution electrode.
8. An acidic electrolytic oxygen anode electrode, characterized in that: The invention comprises an anode carrier and a catalyst material loaded thereon, wherein the catalyst material is an iridium oxide nanocluster oxygen evolution electrocatalyst loaded with zirconium dioxide and prepared by the method according to any one of claims 1 to 5.
9. A method for electrolyzing water, characterized in that: The acidic electrolytic oxygen-splitting anode electrode according to claim 8 is used as the anode.
10. The method for electrolyzing water according to claim 9, characterized in that: in, The electrolyte is 0.5M HClO4 solution or deionized water.
Citation Information
Patent Citations
Tetragonal phase zirconium dioxide with carbon stability under normal temperature and pressure and preparation method
CN105036099A
Preparation method of iridium oxide catalyst for hydrogen production through water electrolysis
CN114540865A
Iridium oxide catalyst and preparation method thereof
CN118007168A
Iridium oxide doped catalyst as well as preparation method and application thereof
CN118272834A
Process for manufacturing supported iridium oxygen evolution reaction catalyst, a product thereof and its use
GB202318307D0